FACTORS THAT AFFECT COMPLIANCE TO UNDER FIVE IMMUNIZATIONS AMONG MOTHERS OF AHIAZU MBAISE LOCAL GOVERNMENT AREA, IMO STATE, NIGERIA - AHIZIH, Chidiebere C E; EGEJURU, Jacinta N; CHUKWULEBE, Monica A (Socialscientia: Journal of Social Sciences and Humanities, 2018)
Under-five mortality remains high in sub-Saharan Africa despite global decline. One quarter of these deaths is preventable through interventions such as immunization. Immunization has been one of the most significant and cost-effective public-health interventions to decrease childhood morbidity and mortality. Reasons for the low coverage of immunization vary from logistic ones to those dependent on human behaviour. This study aimed to examine factors that affect compliance to under-five children immunizations among mothers of Ahiazu Mbaise local government area, Imo state, Nigeria. This study employed the descriptive cross-sectional research design. Systematic sampling method was used to select the households while the women were purposively selected. In all, 160 houses were sampled. The instrument of data collection was the questionnaire and the method of data analysis was quantitative with simple percentage employed for measurement. Formulating strategies to break down the barriers to immunization compliance are not beyond our reach. Maternal education about the concept and value of immunization and improving health worker motivation can significantly contribute to enhance vaccination status. This study serves as an eye opener to the government to continue promoting National Programme on Immunization (NPI) for it could save and protect the precious lives of our future generations.